PERBEDAAN RERATA PENGETAHUAN IBU HAMIL SEBELUM DAN SESUDAH MENGIKUTI KELAS IBU HAMIL DI PUSKESMAS WANGON II KABUPATEN BANYUMAS TAHUN 2012 - Eliana, Arfiah; Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
Introductions: The preparation of pregnant women is important to face pregnancy, gift baby, parturition, baby treatment by joining pregnant women class can decrease number of maternal mortality rate on 2015 into 102/100000 life birth. Wangon public health center II have not ever held research about pregnant women class especially the development of pregnant women knowledge after joining pregnant women class, even Wangon public health center II have hold pregnant women class since 2010. Objectives: The objectives of this research for knowing the different of average pregnant women knowledge before and after joining pregnant women class in Wangon public health center II Banyumas Regency 2012. Methods: This research is pre experiment research, the one group pre test and post test design with cross sectional data collecting, 62 population of pregnant women. The research instrument was questioner. The data analyze used univariat analytic for knowing frequency distribution and bivariat test pair â€œtâ€ test. Results: Before joining pregnant women class, the average of pregnant women knowledge was 11; minimal 1 maximal 14, after joining pregnant women class the average of pregnant mother knowledge was 14; minimal 12 maximal 14. There was differentiation among the average of pregnant women knowledge before and after joining pregnant women class (p value 0,000 < 0,05) Conclusions and suggestion: there was a acfferance among the average of pregnant women knowledge before and after joining pregnant women class. By giving counseling in pregnant women class is effective to increase pregnant women knowledge so it will be better if midwife must give counseling regularly and Wangon public health center II improving the frequency of pregnant women class meeting. It can decrease of maternal mortality rate Indonesia especially in Banyumas. Â KeywordsÂ Â Â  Â Â : knowledge, pregnant women class